1990
DOI: 10.1111/j.1365-2648.1990.tb01857.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of frequency and sources of nursing job stress perceived by intensive care, hospice and medical‐surgical nurses

Abstract: This study compared the frequency and sources of nursing job stress perceived by 35 intensive care (ICU), 30 hospice and 73 medical-surgical nurses. Analysis of variance revealed no significant differences among the three groups of nurses on the overall frequency of job stress. Post-hoc Tukey tests demonstrated a significant difference in three stress subscales among the three groups. ICU and hospice nurses perceived significantly more stress than medical-surgical nurses related to death and dying; ICU and med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
4

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 28 publications
3
86
0
4
Order By: Relevance
“…Some authors investigated if the sources of stress usually reported in literature were identical or similar for all nurses employed in hospitals, or they differed across hospital departments and nursing specialities (24)(25)(26). Results of these studies revealed signifi cantly higher values of stress factors in relation to the items such as conflicts with physicians, problems with supervisors, and uncertainty concerning treatment in nurses in Intensive Care Units (ICU) compared to other departments.…”
Section: Facing Death and Dying Confl Icts With Physicians Inadequamentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors investigated if the sources of stress usually reported in literature were identical or similar for all nurses employed in hospitals, or they differed across hospital departments and nursing specialities (24)(25)(26). Results of these studies revealed signifi cantly higher values of stress factors in relation to the items such as conflicts with physicians, problems with supervisors, and uncertainty concerning treatment in nurses in Intensive Care Units (ICU) compared to other departments.…”
Section: Facing Death and Dying Confl Icts With Physicians Inadequamentioning
confidence: 99%
“…Results of these studies revealed signifi cantly higher values of stress factors in relation to the items such as conflicts with physicians, problems with supervisors, and uncertainty concerning treatment in nurses in Intensive Care Units (ICU) compared to other departments. Stress situations such as performing procedures that are painful for the patient and fear of making mistakes were also recurrent in critical care nurses (24)(25)(26).…”
Section: Facing Death and Dying Confl Icts With Physicians Inadequamentioning
confidence: 99%
“…Specific factors affecting workers' health within each specialty should be identified to reduce workplace stress. Although the scores of work-related stress scales of nurses differ among departments [33][34][35][36] , few studies have clarified associations between job-related stress factors and psychological and physical health based on the characteristics of each specialty. Therefore, we examined degrees of job-related stress factors as well as mental and physical symptoms, and associations of departments and job-related stress factors with those symptoms by distributing a self-administered questionnaire to nurses in various departments of Japanese acute care hospitals.…”
mentioning
confidence: 99%
“…One study found that intensive care nurses reported fewer stress symptoms than nurses from other areas (Milazzo, 1988), and another found that medical surgical nurses had higher job stress than home care nurses and higher frequency (though not intensity) of stress than the normative comparison groups of professional female employees (Salmond & Ropis, 2005). In contrast, others found no differences in the frequency of stress between groups of ICU, hospice and medical-surgical (Foxall, Zimmerman, Standley & Captain, 1990). Sources of job stress differed by unit, however, with ICU and hospice nurses rating higher stress related to death and dying, and medical-surgical nurses reporting higher stress related to workload (Foxall et al).…”
Section: Discussion Related To Incidental Findingsmentioning
confidence: 94%